A Comparison of Children’s Social Behaviors in Single Mother and Two Parent Families in Japan - Katsurada, Emiko; Ueda, Mizuho (Advances in Social Sciences Research Journal, 2024)
The present study examined the differences between young children from single-mother families and those from two-parent families based on their prosocial behaviors and behavior problems. Mothers’ affectionate parenting was also compared. We collected data using a Japanese online survey company. A total of 335 women who had a 3 to 5-year-old child participated; 51.2% of which were single mothers. The mothers rated their child’s behavior problems and prosocial behavior and answered a questionnaire on affectionate parenting. The results indicated a significant interaction effect of family structure and child’s gender on children’s behavior problems. The scores of girls were significantly higher than those of the boys in single-mother families, whereas no such gender difference was found in two-parent families. Concerning the scores of children’s prosocial behaviors and the mothers’ affectionate physical contact, however, there was no difference between single-mother and two-parent households. Limitations of using internet surveys were discussed.